PSVII-10 Assessment of carcass, meat quality and lipidome of Nellore bulls with high and low residual feed intake. - Vesga, Daniela A [UNESP]; Reis, Irene A [UNESP]; Rodrigues, Rafaela C [UNESP]; Filho, Alexandre S Losi [UNESP]; Ferreira, Christina; Torrecilhas, Juliana [UNESP]; Carvalho, Pedro H V; Machado-Neto, Otavio [UNESP]; Chardulo, Luis Artur L [UNESP]; Baldassini, Welder A [UNESP] (Oxford University Press (OUP), 2025)
Abstract This study aimed to compare carcass characteristics and meat quality between feedlot Nellore cattle (Bos indicus) with divergent residual feed intake (RFI) and to investigate potential differences in meat lipid profile. Ninety-six Nellore bulls (average initial body weight: 362.45 ± 25.6 kg; aged 24-26 months) were evaluated for feed efficiency in a group-pen system equipped with individual monitoring of dry matter intake (DMI) and weight gain. Based on RFI, animals were classified as low RFI (more efficient; -1.22 kg/day; n = 20) or high RFI (less efficient; 1.33 kg/day; n = 20). After 120 days on feed, bulls were slaughtered at an average final weight of 520 ± 31 kg. Longissimus thoracis samples were collected 24 hours post-mortem from the left half-carcass (between the 12th and 13th ribs), identified, and aged (1–2 °C) for 15 days. Lipid profiling was conducted using multiple reaction monitoring (MRM) profiling mass spectrometry. Carcass and meat quality data were analyzed using ANOVA. Lipidomic data was normalized and subjected to Student’s t-test, PLS-DA, and functional enrichment analysis. Differences (P < 0.05) were observed between RFI groups for DMI (9.14 vs. 10.42 kg/day), feed conversion ratio (6.06 vs. 6.74 kg/kg), and dressing percentage (54.44 vs. 53.23%), with a trend toward a larger ribeye area in low RFI animals (86.05 vs. 82.91 cm²; P = 0.07). Low RFI bulls also had less backfat thickness (4.75 vs. 5.61 mm) and intramuscular fat (1.43% vs. 1.75%; P < 0.05), as well as less myofibrillar fragmentation index (MFI: 53.01 vs. 68.3; P < 0.01). No differences were detected in pH, color (L*, a*, b*), cooking loss, shear force (WBSF), or lipid oxidation (P > 0.05). The lipidomic analysis identified 60 differentially abundant lipid species (P < 0.05), including diacylglycerols, free fatty acids, phosphatidylcholines, phosphatidylethanolamines, sphingomyelins, and triacylglycerols. Efficient bulls had leaner carcasses and less intramuscular fat without negative impacts on WBSF. This is the first study to characterize the lipid molecular composition of Nellore bulls with divergent RFI, revealing lipid classes associated with mitochondrial function and lipid storage that may help explain differences in cattle feed efficiency and meat quality.